SAE Technical Paper Series 2021
DOI: 10.4271/2021-24-0042
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Field Analysis of Isobaric Combustion Using Multiple Injectors in an Optical Accessible Diesel Engine

Abstract: Isobaric combustion has shown the potential of improving engine efficiency by lowering the heat transfer losses. Previous studies have achieved isobaric combustion through multiple injections from a single central injector, controlling injection timing and duration of the injection. In this study, we employed three injectors, i.e. one centrally mounted (C) on the cylinder head and two side-injectors (S), slantmounted on cylinder head protruding their nozzle tip near piston-bowl to achieve the isobaric combusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The peak motoring pressure (PMP) of CDC and isobaric combustion were fixed at 50 and 70 bar respectively with the peak cylinder pressure (PCP) of 70 bar selected for both cases. This is consistent with our previous studies [12][13][14]. The desired PMPs were attained using intake air pressure of ~1.7 bar for CDC and ~2.2 bar for isobaric combustion.…”
Section: The Optical Engine Test Facilitysupporting
confidence: 92%
See 3 more Smart Citations
“…The peak motoring pressure (PMP) of CDC and isobaric combustion were fixed at 50 and 70 bar respectively with the peak cylinder pressure (PCP) of 70 bar selected for both cases. This is consistent with our previous studies [12][13][14]. The desired PMPs were attained using intake air pressure of ~1.7 bar for CDC and ~2.2 bar for isobaric combustion.…”
Section: The Optical Engine Test Facilitysupporting
confidence: 92%
“…The piston bowl is 22 mm deep and the entire piston is made up of quartz. Compared to the ω-shaped piston used in our previous studies [14,23], a flat-bowl piston is preferred such that the distortion correction from the bottom-view imaging can be circumvented. One of the side quartz windows of the windows holder was utilized for background illumination during Mie scattering imaging, while the other windows were unused.…”
Section: The Optical Engine Test Facilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous works on isobaric combustion employing multiple injectors revealed that using an optimized combination of side and central injectors resulted in higher gross indicated efficiency and lower soot emissions [22]. A recent numerical study [23] shows that by optimizing the side injectors' orientation and the number of holes in the nozzle, the vortical structures near the bowl-wall can be suppressed, leading to a reduction in the soot emissions.…”
Section: Introductionmentioning
confidence: 99%